Inheritance in Shariah Law and Adat Perpatih a comparative study / Noor Jihan Noor Yadah - Noor Yadah, Noor Jihan (Faculty of Law, 1987)
Shariah as a technical term means the Canon Law of Islam, and totally of Allah's (s.w.t) commandments. The Malay community may be classified into two difference groups, one following Adat Temenggong and the other Adat Perpatih. Though both the adat originated from tribal organisations in the past, it is in Adat Perpatih that the remnants of tribal structure are clear. This project looks at inheritance aspect in shariah law in Adat Perpatih in Malaysia.